Pope Francis’ dialogue with Eastern Christians and Protestants - Sawa, Przemysław (Verbum et ecclesia, 2025)
The article addresses Francis’ involvement in ecumenical dialogue with the Orthodox Churches, Oriental Churches and communities arising from the Reformation, including both historical denominations (Anglicanism, Lutheranism, Calvinism and Methodism) and contemporary evangelical movements, particularly Pentecostalism. Francis’ pontificate has been characterised by a strong emphasis on the search for unity among Christians, which is supported by both theological and practical justifications, such as the challenges of modern times and the need for a unified testimony. This article synthesises an analysis of Francis’ individual statements and activities. The research indicates that in his dialogue with Eastern Christians, Francis focused on their spiritual heritage, the relationship between synodality and the Primacy of Peter and the manner in which the papal office is exercised. Additionally, he highlighted the importance of church collaboration in addressing contemporary issues, including peace, ecological concerns and support for those persecuted for their faith. In dialogue with Protestant communities, Francis emphasised the significance of the word of God, spirituality, unity in diversity, a fresh interpretation of the Reformation and its aftermath, the importance of witnessing faith and the role of service in addressing global challenges. Intradisciplinary and/or interdisciplinary implications: A key focus was interaction with Evangelicals, particularly Pentecostals, who are the fastest-growing branch of Christianity. This area emphasises the importance of baptism in the Holy Spirit, evangelisation and the pursuit of unity. Catholic charismatic renewal groups can assist in this mission.